(3JSGeM GdZQH eY GdeSdejf aj GdYUQ GdMGVQ (B:s (3OQGSI fbOjI aj VhA GdESdGe (B/s - (3GdMSjf, YHO GddWja Hf EHQGgje Hf YHO GddWjas ((3GdOeGe (B- (3GdSYhOjI (B:s (3OGQ GHf GdLhRj ddfTQ hGdJhRjY,s, 1999)
(3jJfGhd cJGH (B((3JSGeM GdZQH eY GdeSdejf aj GdYUQ GdMGVQ(B) (3hGdPj bGe HJCdjag YHO GddWja Hf EHQGgje Hf YHO GddWja GdMSjf, aj MhGdj (B(480) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3JSGeM GdZQH eY GdeSdejf(B) (3GdcJGH OQGSI JSYi dJMQjQ GdeaGgje hHjGf GdUhGH, aj GdJSGeM GdUMjM GdPj LGA Hg GdESdGe(B. (3hGdeYfi GdPj jJQOO cKjQG Ydi CdSfI GdZQHjjf hGdeNGda ddJUhQ GdESdGej aj YdGbI GdeSdejf HZjQge(B. s
Keywords: (3GdESdGe hGdZQHs; (3GdESdGe hGdYdGbGJ GdNGQLjIs